2017
DOI: 10.3389/fpls.2017.01062
|View full text |Cite
|
Sign up to set email alerts
|

The C4 Model Grass Setaria Is a Short Day Plant with Secondary Long Day Genetic Regulation

Abstract: The effect of photoperiod (day:night ratio) on flowering time was investigated in the wild species, Setaria viridis, and in a set of recombinant inbred lines (RILs) derived from a cross between foxtail millet (S. italica) and its wild ancestor green foxtail (S. viridis). Photoperiods totaled 24 h, with three trials of 8:16, 12:12 and 16:8 light:dark hour regimes for the RIL population, and these plus 10:14 and 14:10 for the experiments with S. viridis alone. The response of S. viridis to light intensity as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 65 publications
0
15
0
1
Order By: Relevance
“…chinensis as an example, the multiyear average AT over the growing season ranged from 2,206 at Ergun to 2,732 degree days at Xilinhot (Table ). Previous studies indicated that the day length affected the phenologies of certain grasses (Benedict, ; Cookson et al, ; Doust et al, ). The mean day length over the growing season at Ergun was 0.6 hr longer than at Xilinhot, suggesting that L .…”
Section: Resultsmentioning
confidence: 98%
“…chinensis as an example, the multiyear average AT over the growing season ranged from 2,206 at Ergun to 2,732 degree days at Xilinhot (Table ). Previous studies indicated that the day length affected the phenologies of certain grasses (Benedict, ; Cookson et al, ; Doust et al, ). The mean day length over the growing season at Ergun was 0.6 hr longer than at Xilinhot, suggesting that L .…”
Section: Resultsmentioning
confidence: 98%
“…Similarly, to study the effect of different stress conditions on adult plants, control plants should grow in conditions that result in optimal growth and development. It is known that Setaria growth and development is extremely sensitive to photoperiod and temperature ( Swanton et al, 1999 ; Doust et al, 2017 ). As expected, huge differences in overall plant architecture were observed between plants grown in controlled environment growth chambers versus controlled environment greenhouses.…”
Section: Resultsmentioning
confidence: 99%
“…Thus selection on flowering time is unlikely to be a direct response to domestication but is best considered as a target for crop improvement. However, flowering time and photoperiod sensitivity also interact with other important traits, such as branching, height and biomass ( Doust, 2017 ; Doust et al, 2017 ), making it relevant to discuss here.…”
Section: Genes Contributing To Domestication-related Traitsmentioning
confidence: 99%
“…A recent multiplexed shotgun genotyping (MSG) resequencing analysis of 439 RILs (derived from a cross between foxtail millet accessions Zhanggu and A2) under short (<12 h light) and long photoperiods (>14 h light), uncovered a total of 59 QTLs for 14 agronomic traits which were influenced by different photoperiods ( Zhang K. et al, 2017 ). Doust et al (2017) examined flowering responses in short (8 or 12 h light) and long (16 h light) photoperiods in a QTL mapping population, and demonstrated differences between short and long day regulation, with the 8 and 12 h photoperiods sharing QTL on chromosomes 4 and 5, and the 12 and 16 h having a shared QTL on chromosome 8. In addition there were QTLs on chromosomes 2 and 3 that were unique to the 16 h photoperiod.…”
Section: Genes Contributing To Domestication-related Traitsmentioning
confidence: 99%